Preference of Underutilized Vegetables in Traditional Manipuri Cuisine: Delicacy and Health Benefits - Chanu, T. M.; Phurailatpam, A.K.; Singh, S.R. (Indian Journal of Hill Farming, 2019)
The North Eastern region of India comprising of eight states namely Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram, Nagaland, Tripura and Sikkim, is one of the richest reservoirs of different underutilized vegetable crop species (UVCS). These underutilized or underexploited plants are used or consumed in many forms as raw or cooked by the local people. As differed from the other parts of the country, the underutilized vegetable species are found abundantly in this part of the region and it forms an important part of the local food and cuisines. Various delicacies and products are prepared comprising of the various UVCS along with meat and fish. Apart from the nutritional value, these UVCSs are used for medicinal purposes, for income generation and poverty alleviation. Some of these crop species may be widely distributed globally, but are restricted to a more local production and consumption system. With good adaptation to often marginal lands, they constitute an important part of the local diet of communities providing valuable nutritional components, which are often lacking in staple crops. The local delicacies prepared from UVCS are a must in the everyday lives of the people and sometimes it is even more prominent and important than the standard staple crops and vegetables. Here, an effort has been made to list out the various underutilized crop species and the delicacies prepared from them by the local people of Manipur. Research attentions and interests should be taken in these underutilized crops for exploring new food crops and also food security of the country.